(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To review of clinical and paraclinical characteristics of the group of patients who had frozen embryo transfer using timelapse system for embryo incubation. Subjects and methods: Cross-sectional descriptive study on 118 cases of embryo culture using Timelapse monitoring system at the Department of Assisted Reproduction and Andrology, Hanoi Obstetrics and Gynecology Hospital from December 2023 to May 2024. Results: The average age of the wife was 31.9 ± 4.6 years; the average duration of infertility was 2.84 ± 2.2 years, the group of infertility under 5 years accounted for the highest rate of 80.4%. 86.8% of patients had experienced two or more miscarriages or stillbirths in their past. At the start of the cycle, the average concentration of FSH was 6.75 ± 3.15 mIU/mL. 3.84 ± 2.61 ng/mL was the average AMH levels. 14.01 ± 7.11 antral follicles on average were present. There was no decline in ovarian reserve in 91.5% of patients. Conclusions: Timelapse is the preferred option for patients with a history of multiple miscarriages or stillbirths, recurrent implantation failure, and normal endocrine and ovarian reserve characteristics.